Srr2, a multifaceted adhesin expressed by ST‐17 hypervirulent Group B Streptococcus involved in binding to both fibrinogen and plasminogen. Issue 6 (17th July 2015) - Six, Anne; Bellais, Samuel; Bouaboud, Abdelouhab; Fouet, Agnès; Gabriel, Christelle; Tazi, Asmaa; Dramsi, Shaynoor; Trieu‐Cuot, Patrick; Poyart, Claire
Summary The Group B Streptococcus (GBS) 'hypervirulent' ST‐17 clone is strongly associated with invasive neonatal meningitis. Comparative genome analyses revealed that the serine‐rich repeat (Srr) glycoprotein Srr2 is a cell wall‐anchored protein specific for ST‐17 strains, the non‐ST‐17 isolates expressing Srr1. Here, we unravel the binding capacity of GBS Srr proteins to relevant components of the host fibrinolysis pathway. We demonstrate that: (i) Srr2 binds plasminogen and plasmin whereas Srr1 does not; (ii) the ability of ST‐17 strains to bind fibrinogen reflects a high level surface display of Srr2 combined with a higher affinity of Srr2 than Srr1 to bind this ligand; and (iii) Srr2 binding to host plasma proteins results in the formation of bacterial aggregates that are efficiently endocytosed by phagocytes. Importantly, we show that Srr2 increased bacterial survival to phagocytic killing and bacterial persistence in a murine model of meningitis. We conclude that Srr2 is a multifaceted adhesin used by the ST‐17 clone to hijack ligands of the host coagulation system, thereby contributing to bacterial dissemination and invasiveness, and ultimately to meningitis.